New Arabic Loanwords In Indonesian Dictionary - Mohammad Rokib; Syamsul Sodiq; Moh. Mudzakkir (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2023)
This paper explores the development of the new Arabic loanwords in the Indonesian language during the second half of the Reform Era. The study examines primary and secondary sources to identify recent Arabic loanwords, which conclude six relevant words: ‘kalas‘, ‘qurani‘, ‘islah‘, ‘kafah‘, ‘ajib‘, and ‘harem‘. The analysis reveals that kafah and ajib have been added recently to the online dictionary edition, Kamus Besar Bahasa Indonesia (KBBI). The KBBI identified kafah as an Arabic loanword, while ajib transformed its vocal articulation and is now recognized as a loanword. The research also sheds light on the influence of Arabic on the Indonesian language. This paper contributes to the understanding of the development of the Indonesian language and the role of loanwords in shaping the language. The study's findings also highlight the importance of language standardization and the role of dictionaries in shaping and reflecting the linguistic landscape of Indonesia.